The selected letters of Norman Mailer - Mailer, Norman 1923-2007 (Random House, 2014)
"Mailer wrote almost 50,000 letters over the course of his life, keeping a copy of almost every one of them. He corresponded with presidents and politicians, artists and athletes, writers and editors, students, antagonists, fans, friends, his children, his loves, including his beloved sixth wife, Norris Church Mailer. Here are the letters of a precocious sixteen-year-old arriving from Brooklyn at Harvard. Here are the letters depicting the horrors of the war in the Pacific from a soldier's point of view. Here are the letters describing a young writer's struggle with his first novel, a manuscript that would become The Naked and the Dead. And here are the many, many letters of a man who spent sixty years in the spotlight. Read together, they form an autobiographical portrait of Norman Mailer"--
Includes bibliographical references and index
Keywords: Mailer, Norman / Correspondence; Mailer, Norman; Mailer, Norman -- 1923-2007; Briefsammlung